2010
DOI: 10.1074/jbc.m110.185629
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-driven Reconstruction of Acinetobacter NAD Metabolism

Abstract: Enzymes involved in the last steps of NAD biogenesis, nicotinate mononucleotide adenylyltransferase (NadD) and NAD synthetase (NadE), are conserved and essential in most bacterial species and are established targets for antibacterial drug development. Our genomics-based reconstruction of NAD metabolism in the emerging pathogen Acinetobacter baumannii revealed unique features suggesting an alternative targeting strategy. Indeed, genomes of all analyzed Acinetobacter species do not encode NadD, which is function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 48 publications
(79 reference statements)
2
46
0
Order By: Relevance
“…Other than the classical Preiss-Handler pathway outlined above, alternative pathways for salvage of NAD exist in a number of lineages. Known examples include the relatively rare non-deamidating routes, like the salvage of nicotinamide in F. tularensis that is performed by combined activity of a nicotinamide phosphoribosyltransferase (nadV) and a NMN adenylyltransferase (NadM, in some lineages is also a NaMN adenyltransferase), 12,52 or the salvage of ribosylnicotinamide (RNm) by the bifunctional N-ribosylnicotinamide kinase/NMN adenylyltransferase NadR and its associated RNm transporter PnuC 13,53 found in enterobacteriaceae and some other bacteria. In F. tularensis, the enzyme NMN synthetase, a paralog of NadE, provides a unique path for de novo synthesis of NAD from tryptophan in the absence of NadD via the amidation of NaMN.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other than the classical Preiss-Handler pathway outlined above, alternative pathways for salvage of NAD exist in a number of lineages. Known examples include the relatively rare non-deamidating routes, like the salvage of nicotinamide in F. tularensis that is performed by combined activity of a nicotinamide phosphoribosyltransferase (nadV) and a NMN adenylyltransferase (NadM, in some lineages is also a NaMN adenyltransferase), 12,52 or the salvage of ribosylnicotinamide (RNm) by the bifunctional N-ribosylnicotinamide kinase/NMN adenylyltransferase NadR and its associated RNm transporter PnuC 13,53 found in enterobacteriaceae and some other bacteria. In F. tularensis, the enzyme NMN synthetase, a paralog of NadE, provides a unique path for de novo synthesis of NAD from tryptophan in the absence of NadD via the amidation of NaMN.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,[50][51][52][53][54][55] While there is diversity in the NAD-centered pyridine nucleotide cycle across bacteria, especially in terms of the different routes of salvage and overlap with de novo synthesis, the following key enzymes have been recognized as key players in the pathway ( Fig. 1): 12,13,[50][51][52][53][54][55] (1) a multi-domain carboxylating nicotinate/ quinolinate phosphoribosyltransferase (nadC in Fig. 1) capable of synthesizing nicotinate monophosphate ribonucleotide (NaMN) from quinolinic acid during de novo synthesis of NAD; (2) the PncA nicotinamidase that initiates the classical salvage arm of the pathway by catalyzing the hydrolysis of free nicotinamide (NM) to nicotinate (NaM); (3) the nicotinate phosphoribosyltransferase pncB, a TIM barrel enzyme of the NAPRTase family, that transfers a phosphoribosyl moiety to nicotinate thus generating nicotinate D-ribonucleotide (NaMN); (4) a HIGH nucleotidyltransferase (NadD) that adenylates the nucleotide formed in the prior steps using ATP to form the dinucleotide; (5) a PP-loop fold NAD synthase (NadE) that adenylates the carboxyl group of nicotinate using ATP and subsequently ligates it to ammonia to form a nicotinamide moiety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome annotation, single-gene deletion mutants, enzyme kinetics, and chromosomal expression of heterologous genes revealed alternative NAD metabolism which showed that current drug targets, NadD and NadE, are absent or dispensable in A. baylyi (48). Thus, NadM, which is unconditionally essential in A. baylyi, is proposed as an alternative drug target for the multidrug-resistant pathogen A. baumannii (48,49). Similar approaches were used to predict and validate a pathway to consume D-glucarate, including its regulatory mechanisms (50).…”
Section: Elucidation Of Metabolic Pathways and Novel Biochemistrymentioning
confidence: 99%